Mosse Lecture #24 - Mosse, George L. (George Lachmann), 1918- (My University, 1982)
For more information, check out the George Mosse website at http://mosseprogram.wisc.edu/
46:56 minutes
Keywords: European cultural history, 1660-1870; Europe--History